Differences in Organoleptic Quality and Nutritional Value of Profile of Tuna Fish Floss with Addition of Jackfruit Dami as an Alternative Source of Protein and Fiber: Perbedaan Mutu Organoleptik dan Profil Nilai Gizi Pada Abon Ikan Tuna Dengan Penambahan Dami Nangka Sebagai Alternatif Sumber Protein dan Serat - Azis, Rahmatullah Farid; Jumiyati, Jumiyati; Yulianti, Risda (Universitas Slamet Riyadi Surakarta, 2024)
Fish floss is a processed fishery product made from fresh fish as raw material in the form of powder or fiber from fish meat. The seasoning given has a brownish color which goes through boiling, steaming, shredding, adding spices and the cooking process. Jackfruit dami contains 1.94% crude fiber. Due to its high fiber content, Dami jackfruit has the potential to be processed into food products and is a good source of fiber in making shredded meat. This research aims to determine the differences in organoleptic hedonic tests and hedonic quality and nutritional value profile of tuna fish floss with the addition of jackfruit dami as an alternative source of protein and fiber. The design used was a completely randomized design with 3 different treatments between tuna (gr) and jackfruit dami (gr) F1 (75:25), F2 (50:50), and F3 (25:75). The results of this study showed that the F2 treatment had a level of preference for color (3.93), taste (3.67), texture (3.63), aroma (3.63), and overall (3.67). Color, texture and overall have significant differences in panelists' preferences, but the aroma and taste aspects are not significant in panelists' preferences. The best treatment, F2, has a water content of 7.08%, protein content of 48.1%, and fiber content of 3.50%.